Exploring the functional properties and nutritional values of colored oyster mushrooms species (Pleurotus, Agaricomycetes): a review - Medihi, Nurul Izzati; Abdul Haiyee, Zaibunnisa; Patmawati, .; Sukor, Rashidah; Raseetha, Siva (Begell House, 2024)
Colored oyster mushrooms species of genus Pleurotus are a variety of edible mushrooms that attract a lot of interest among the consumers and scientists due to its scientific evidence that they have promising health benefits. However, information on their characteristics and properties is still scarce. Consequently, it is important to determine the potential health benefits of the mushrooms. This review paper presents an overview of functional properties and nutritional values of colored oyster mushrooms (Pleurotus spp.). It particularly discusses the types of pigments present in Pleurotus spp., their characteristics, and potential nutritional values. Pigments such as melanin, carotenoids, and flavonoids are reported to be present in colored oyster mushrooms. Moreover, the antioxidant compounds of these mushrooms have been unveiled, demonstrating their potential to counteract oxidative stress and improve general health. In addition, the investigation into the nutritional characteristics of the mushrooms reveals encouraging aspects for their incorporation into dietary considerations. Thus, it can be concluded that colored Pleurotus species have an immense amount of potential for use as natural colorants, as well as nutritious and antioxidant-rich compounds. These mushrooms represent an important advancement in the search for functional foods due to their significant nutrients such as proteins, amino acids, carbohydrates, and fibers.